Analysis of direct interconnection technique for offshore airborne wind energy systems under normal and fault conditions. (February 2019) - Salari, Mahdi Ebrahimi; Coleman, Joseph; Toal, Daniel
Abstract: Direct interconnection is a novel technique for interconnecting offshore airborne wind energy (AWE) generators which facilitates the removal of power converters from the offshore generation site. In this technique, unlike the conventional approach, all generators are interconnected directly and after dispatching the generated power to shore, a back to back converter or several paralleled back to back converters change the generated power to grid-compliant power. Considering that the high expenses of offshore operations for back to back converter repair and maintenance and the higher accessibility of shore-side back to back converters, this technique can improve the reliability and economy of the energy generation system. This research aims to implement and study the practicality and reliability of the direct interconnection approach for offshore non-reversing pumping mode airborne wind energy generator systems. The interaction of direct interconnected AWEs in normal and fault conditions is investigated, and synchronisation, frequency control and load sharing control of the AWE farm are examined and discussed. Highlights: An offshore non-reversing pumping mode airborne wind energy (AWE) farm has been modelled and simulated. Feasibility and reliability for direct interconnection technique for non-reversing pumping mode offshore AWE farms has been developed and implemented, and the feasibility and reliability of this method for non-reversing pumping mode AWE systems have been studied and examined. The operation of the directly interconnected AWE systems under normal and fault conditions has been investigated.